Investigation of Philosophical Content in Design Education, The Case of Deleuze and Guattari - Ardatürk, Ahmet Sadi (Architecture Image Studies, 2024)
Design education exists in a chaotic and multidisciplinary structure in accordance with its own essence. Many different paradigms that exist on different layers create a complex pattern that the student must come to terms with and make sense of in the educational process. This pattern offers a model that is both high effort and high quality. Within this model, philosophy is one of the most effective tools for understanding and making sense of the essence of design, establishing a design relationship on concept, and ensuring design culture and intellectual identity. However, in the process of design education, this important part is relatively left out and educational models are shaped through materialist realities. This study focuses on this very point, the questioning of philosophical meaning in design education. A case study was conducted on the understanding of philosophical meaning and students' reactions and responses to this area were measured. At this point, the concepts and discourses of Deleuze and Guattari, which are particularly and deliberately difficult to understand and make sense of, were preferred as philosophical discourse. Dealing with these concepts constitutes the example of one of the most difficult confrontations possible. In the study, it was ensured that the students designed the concepts they did not know both without knowledge and then redesigned them with the research they did on their own, and conceptual questioning was made between the two studies. As a result, data were obtained on the use of philosophical content and thought systematics in design education. The appropriateness of the use of philosophical content in design education has been revealed.